The Associations of Plasma Carotenoids and Vitamins With Risk of Age-Related Macular Degeneration: Results From a Matched Case-Control Study in China and Meta-Analysis - Jiang, Hong; Fan, Yahui; Li, Juan; Wang, Jiaqi; Kong, Liyun; Wang, Lina; Li, Zhaofang; Ma, Mei; Shi, Xin; Liu, Sijiao; Shi, Jia; Zhu, Hailu; et al. (Frontiers in Nutrition, 2022)
Background and purpose: Data from studies support a beneficial effect of carotenoids and vitamins on age-related macular degeneration (AMD) risk. However, studies on the relations between blood levels of these nutrients and AMD are limited and provide conflicting results. The objective of this case-control study and meta-analysis was to examine whether the blood concentrations of carotenoids and vitamins were associated with the risk of AMD. Methods: A total of 164 cases of AMD and an equal number of controls individually matched according to age and gender among participants that provided blood samples in the Xi'an Eye Study. Plasma carotenoids and vitamins were measured using reversed-phase high-performance liquid chromatography. Bonferroni-corrected covariate-adjusted conditional logistic regression was used to estimate AMD risk by category of these nutrients in the multivariable-adjusted model. Results: Plasma concentrations of carotenoids and vitamins were significantly lower in patients with AMD than those in controls. After multivariate adjustment for body mass index, blood cholesterol, and other lifestyle risk factors, higher lutein/zeaxanthin content in plasma was significantly associated with a decreased risk of AMD, and the odds ratio (OR) comparing the top and bottom tertiles was 0.21 (95%CI: 0.05,0.84; Ptrend=0.024). Associations for β-carotenes (OR:0.11; 95%CI: 0.02,0.50; Ptrend<0.001), and β-cryptoxanthin (OR:0.08, 95%CI: 0.02,0.39; Ptrend<0.001) were similar to that for lutein/zeaxanthin. Inverse associations were also observed for a higher level of retinol (OR:0.14, 95%CI: 0.03,0.61; Ptrend=0.006) and α-tocopherol (OR:0.25, 95%CI: 0.06, 0.98; Ptrend=0.006). In the meta-analysis, a protective effect was detected for AMD among participants with high blood lutein/zeaxanthin level (OR:0.53, 95%CI: 0.40,0.72, P<0.001) compared to those with low level. Similar inverse associations were seen for β-carotene (OR:0.48, 95%CI: 0.28,0.84, P=0.010), β-cryptoxanthin (OR:0.48, 95%CI: 0.23,1.00, P=0.049), lycopene (OR:0.70, 95%CI: 0.54,0.90, P=0.006) and α-tocopherol (OR:0.50, 95%CI: 0.31,0.81, P=0.005). Conclusions: Results of the case-control study were consistent with findings from the meta-analysis, indicating that higher concentrations of carotenoids and vitamins were inversely associated with the AMD risk. Our finding supports the current notion that these nutrients are likely to affect the development of AMD and may help to refine strategies for the prevention of age-related eye diseases.